Customer perception towards Canon digital camera / Sheikh Shafizal Sheikh Ilman - Sheikh Ilman, Sheikh Shafizal (2010)
This study is about the factors on customer perception towards Canon Digital Camera. This study was started with the introduction of the study, the literature review which can support the study and it followed by the methodology used in conducting the study. A survey of questionnaire was personally administered to the 50 employees at around Shah Alam shopping malls. The sample was used the convenience random sampling whereby all the customers have the same probability to answer the questionnaires. Overall, majority of the customers feel neutral on the factors; product, promotion place and price factors. The questionnaires which of they answered shows their neutrality towards the statement. They also have reported that Canon digital camera is expansive. They have put place as the most influential factors towards the perception towards Canon digital Camera. They also feel that their perception will be different if Canon change they price on the digital camera.